The Effects of Adjuvant Chemoradiotherapy on Survival in Patients with Primary Laryngeal Cancer with Close Surgical Margins and Positive Surgical Margins - Inanc, Berrin; Inanc, Kubilay; Bilici, Suat; Cakir, Mustafa; Yigit, Ozgur (KARE PUBL, 2020)
OBJECTIVE The gold standard treatment for squamous cell carcinoma of the larynx is a resection of the primary tumour with negative surgical margins. In this study, we retrospectively investigated the effects of adjuvant concurrent chemoradiation on the survival rates of laryngeal cancer with close surgery margins and patients with positive surgery margin. METHODS A total of 40 patients treated with concurrent chemoradiation were included in this study. All of these patients had surgery for laryngeal cancer and had received 66 Gy (2Gy/fr) of radiotherapy and concurrent weekly cisplatin. Patients were stratified into two groups according to surgical margin status. Members of group 1 had a positive surgery margin

group 2 patients had close surgical margins and were studied for comparative analyses. RESULTS At the median follow-up of 40 months, nine patients (44.4\%) experienced local/regional failures, six of which were detected on the second follow-up. In patients with positive surgical margin, overall survival (OS), disease-free survival (DFS), and loco-regional progression-free survival (LRPFS) were 59\%, 44\% and 81\%, respectively. OS, DFS and LRPFS for those with close surgical margins were 57\%, 46\% and 71\%, respectively. No statistically significant differences related to OS, DFS, and LRPFS were observed between groups 1 and 2 (p=0.802, p=0.610 and p=0.383, respectively). On univariate Cox-regression analysis, the presence of perineural invasion and lymphovascular invasion was statistically significant for OS and DFS (p=<0.05). Being 65 years old or above was statistically significant for OS (p=<0.05). CONCLUSION Although limited by small sample size, our results revealed that there was no significant difference between close and positive margins in terms of OS, DFS and LRFS. More detailed and comprehensive studies on the close surgical margin (2 mm, 3 mm and 4 mm) are needed.
Keywords: Concurrent chemoradiotherapy; close surgical margin; laryngeal cancer; positive surgical margin